1962
DOI: 10.2307/1420286
|View full text |Cite
|
Sign up to set email alerts
|

Pictorial Recognition as an Unlearned Ability: A Study of One Child's Performance

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0
3

Year Published

1981
1981
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(114 citation statements)
references
References 0 publications
4
106
0
3
Order By: Relevance
“…Children's understanding of objects and space emerges gradually under their development (Piaget and Inhelder 1956). Some studies show that children of two years recognize a real object from a picture even when they have never seen it in real life (Hochberg and Brooks 1962;Daehler, Perlmutter et al 1976;Harris, Kavanaugh et al 1997;Tomasello, Striano et al 1999;Striano, Rochat et al 2003;Younger and Johnson 2004). Other studies have found that children recognize the relationship between objects and pictures successfully when they are about one year old, but these are 3D models and 2D pictures made for the studies that are simpler than those in the real world (Rose, Gottfried et al 1983;Skouteris, McKenzie et al 1992;Younger and Johnson 2006).…”
Section: Comparing Different Shape Dimensionsmentioning
confidence: 99%
“…Children's understanding of objects and space emerges gradually under their development (Piaget and Inhelder 1956). Some studies show that children of two years recognize a real object from a picture even when they have never seen it in real life (Hochberg and Brooks 1962;Daehler, Perlmutter et al 1976;Harris, Kavanaugh et al 1997;Tomasello, Striano et al 1999;Striano, Rochat et al 2003;Younger and Johnson 2004). Other studies have found that children recognize the relationship between objects and pictures successfully when they are about one year old, but these are 3D models and 2D pictures made for the studies that are simpler than those in the real world (Rose, Gottfried et al 1983;Skouteris, McKenzie et al 1992;Younger and Johnson 2006).…”
Section: Comparing Different Shape Dimensionsmentioning
confidence: 99%
“…Pretechnological cultures produce costumes, totems, musical instruments, and tools that depict people or animals. Representational objects are historically and culturally ubiquitous, they have aesthetic, cultural, or ritual importance, and young children require little if any experience to perceive their depictive properties (Hochberg & Brooks, 1962). For these reasons, inability to coordinate representational and functional aspects would be a striking deficit.…”
Section: Experimental Rationalementioning
confidence: 99%
“…The common assumption that line-drawing recognition is a learned or cultural phenomena is not supported by the evidence. In a convincing test of this conjecture, Hochberg and Brooks [15] describe the case of a 19-month-old human baby who had had no previous exposure to any kinds of two-dimensional images, yet was immediately able to recognize ordinary line drawings of known objects. It is true that there has been some research on the bottom-up derivation of depth directly from line drawings or the edges detected in a single image [2,3,27], including previous research by the author [20].…”
Section: Role Of Depth Reconstruction In Human Visionmentioning
confidence: 99%